Litisconsorcio e Intervención de Terceros en el Proceso Civil: Buscando una Nueva Aproximación - Prado Bringas, Rafael (2016)
This article addresses the treatment of the joinder and the intervention of third parties in the Civil Procedure Code. The authors examines the procedural institutions for try provide the right interpretation of the procedure rules concerning to the material and get a true effective jurisdictional protection.